KAJIAN KEBERLANJUTAN USAHA BUDIDAYA RUMPUT LAUT Eucheuma cotonii DI PERAIRAN DUSUN WAEL KABUPATEN SERAM BAGIAN BARAT - Matakupan, Jolen; Pattipeilohy, Christian E.; Tuhumury, Semuel F.; Sahetapy, Jacqueline M. F.; Louhenapessy, Daniel G. (Balobe: Jurnal Pengabdian Masyarakat, 2025)
Seaweed is one of the leading types of aquaculture commodities with competitive market economic value in both domestic and export markets. This is partly because in addition to functioning as food, it is also due to the diversification of seaweed products that have. Wael Hamlet is one of the hamlets located in Piru Village, West Seram District. The majority of people in Wael Hamlet work as fishermen and cultivators, both fish farming and seaweed cultivation. Wael Hamlet is one of the E. Cottoni producing areas in West Seram Regency. The existing condition of seaweed cultivation in Wael Hamlet is currently experiencing a decline and even the fishermen do not produce seaweed. The conclusion of this activity is that the eucheuma cotonii seaweed cultivation business in the hamlet of Wael, West Seram Regency has decreased production due to disease attacks and pests in the form of baronagn fish and also turtles.